Optimizing heavy crude oil conversion: Catalytic thermolysis with TiO2@α-Fe2O3 nanocomposite and surfactant dynamics - Asmaa S. Morshedy; Tahany Mahmoud (Petroleum)
Currently, as the production of light crude oil is reaching its peak, the focus of the petroleum industry is shifting towards significant amount of heavy oil to meet the increasing need for energy and fuels. Heavy oil is typically categorized by its high density, great viscosity with small API gravity, high hetero-atom content and limited low boiling point fuel fraction yield compared to light oil. One approach for enhancing the flow characteristics of heavy oil before the recovery process is introducing catalysts into the reservoir. This scientific research focuses on the preparation and characterization of (10%, 20%, 30%) TiO2@α-Fe2O3 nanocomposite catalysts for potential catalytic applications. The study outlines the synthesis method used to create different ratios of as-prepared nanocomposites. It provides detailed characterization through various analytical techniques. The results highlight the successful formation of X% TiO2@α-Fe2O3 nanocomposites with well-defined structures and optimized properties for catalytic reactions. The study investigates the impact of this nanocomposite on the rheological characterizations of heavy crude oil, focusing on the capability of decreasing viscosity and advance flow characteristics. The experimental results demonstrate notable improvements in viscosity reduction and enhancing heavy crude oil production processes as the best results obtained by (0.5 wt%) 20% TiO2@α-Fe2O3 (62.6% after 2 h at 200 °C). The asphaltene and resin ratio decreased by 54.5% and 68.1% respectively. The saturated and aromatic content shows 67.56% and 15.91% respectively at the same conditions. The presence of different surfactants (non-ionic and anionic) gives a synergetic effect which reveals active participation of contact angle changing and Interfacial tension (IFT) reduction. This research contributes to the advancement of methods for upgrading heavy crude oil, offering a promising avenue for increasing efficiency and productivity in the oil industry.